SUN-292 Adolescent Transgender Females Have an Intermediate Body Composition Between Female and Male Controls - Nokoff, Natalie (J Endocr Soc, 2019)
Background and Objectives: Among youth, 0.7% identify as transgender. Markers of cardiometabolic health and body composition in transgender youth undergoing gender-affirming hormone therapy have not been rigorously studied. Our objectives were to evaluate differences in body composition, insulin sensitivity, lipid profile, and aspartate and alanine aminotransferases (AST, ALT) in male-to-female (MTF) youth treated with estradiol (E2) compared to non-transgender female (FC) and male controls (MC). Methods: Fourteen MTF E2-treated (mean + SD E2 dose 1.5 + 1.0 mg/day, duration 1 + 0.8 years) participants (aged 14.5-19.4 years) were compared to BMI percentile-category-matched and age-matched (within 1 year) FC (n=23, aged 14.2-18.3) and MC (n=24, aged 14.5-19.8). Three MTF participants were also on a gonadotropin releasing-hormone analogue (GnRHa) for suppression of endogenous testicular function. Participants had fasted morning laboratory testing and body composition measured by dual-energy X-ray absorptiometry (DXA). Differences (mean + SD) in body composition, insulin sensitivity (estimated from 1/[fasting insulin]), lipids, leptin, AST, ALT and blood pressure (BP) were evaluated using a mixed linear regression model with a random effect for the matched set. A spearman correlation was performed to evaluate for a correlation between 1/[fasting insulin] and % lean mass. Results: MTF vs. FC: Total testosterone was higher in MTF vs. FC (224 + 182 vs. 43 + 10 ng/dL, respectively, p<0.001); however, the serum E2 was not different between the groups (98 + 135 vs. 96 + 127 pg/mL, respectively, p=0.8). MTF had a lower % fat (31 + 7 vs. 35 + 8%, p=0.03) and higher % lean mass (66 + 6 vs. 62 + 7%, p=0.03) than FC. MTF had a higher AST (37 + 4 vs. 23 + 6 U/L, p<0.001) and higher 1/[fasting insulin] (0.135 + 0.055 vs. 0.098 + 0.045, p=0.04) than FC. MTF vs. MC: Serum E2 was higher (124 + 162 vs. 23 + 9 pg/mL, p=0.005) and total testosterone was lower (252 + 214 vs. 412 + 168, p=0.012) in MTF than MC. MTF had higher % fat (28 + 6 vs. 20 + 10%, p=0.003) and lower % lean mass (69 + 5 vs. 77 + 9%, p=0.001) than MC. MTF had higher HDL (50 + 10 vs. 43 + 6 mg/dL, p=0.02) and leptin (14 + 12 vs. 6 + 9 ng/mL, p<0.001) and lower systolic BP (106 + 11 vs. 116 + 8 mmHg, p=0.007) than MC. 1/[fasting insulin] correlated with % lean mass (r=0.58 [95% CI: 0.37, 0.74], p<0.0001). Conclusions: MTF body composition differences may be explained by a male lean mass accrual pattern during puberty, followed by a gain in % fat and concomitant rise in leptin due to E2 treatment. This is similar to what is seen in adults, but adolescents have not been studied. The higher insulin sensitivity in MTF vs. FC may be explained by differences in lean mass. Longitudinal studies with and without pubertal blockade are now needed to understand the impact of E2 therapy in MTF youth in the absence of exposure to a male pubertal hormonal pattern on body composition and cardiometabolic health.